2009
DOI: 10.1177/1933719109334260
|View full text |Cite
|
Sign up to set email alerts
|

HOXA11 Promotes Fibroblast Proliferation and Regulates p53 in Uterosacral Ligaments

Abstract: The uterosacral ligaments (USLs) are key support structures of the uterus and upper vagina. Previously, we have shown that HOXA11 is necessary for the development of the USLs, is deficient in women with pelvic organ prolapse (POP) and regulates expression of extracellular matrix (ECM) proteins. Here we sought to determine if HOXA11 regulates cell proliferation in the USLs in women. Like others, we have found that, there is decreased cellularity in prolapsed USLs compared to USLs in women with normal pelvic sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 33 publications
(64 reference statements)
0
22
0
Order By: Relevance
“…Decreased synthesis of these fibrils would expectedly reduce the total COLI and COLIII content in the USLs and uterus. Alternatively, decreased collagen production in both USLs and uteri may be a result of decreased proliferation of fibroblasts, as our previous observations showed that Hoxa11 overexpression promoted cell proliferation in murine fibroblasts and in human primary USL cell cultures through a p53-dependent pathway [36].…”
Section: Discussionmentioning
confidence: 92%
“…Decreased synthesis of these fibrils would expectedly reduce the total COLI and COLIII content in the USLs and uterus. Alternatively, decreased collagen production in both USLs and uteri may be a result of decreased proliferation of fibroblasts, as our previous observations showed that Hoxa11 overexpression promoted cell proliferation in murine fibroblasts and in human primary USL cell cultures through a p53-dependent pathway [36].…”
Section: Discussionmentioning
confidence: 92%
“…Furthermore, cultured smooth muscle cells from patients with and without POP would help us to determine if there is a difference in the rate of proliferation and responsiveness to estrogen. Also there are other factors not controlled for in this trial that may have an influence on cell proliferation rates (Connell et al, 2009). Finally, a 3-D culture coculture model may better represent the complex in vivo pelvic floor supportive structures than a monolayer of smooth muscle cells.…”
Section: Discussionmentioning
confidence: 99%
“…Using USL tissue from prolapsed and nonprolapsed women undergoing hysterectomy they found that women with POP have decreased Hoxa11 mRNA expression compared with controls. Hoxa11 also increases proliferation of fibroblasts and human USL cells in vitro and may do so via repression of p53, a known cell-cycle suppressor [50]. Knockdown of Hoxa11 decreases collagen and increases MMP expression in mice mimicking, at least in part, the enzymatic derangements seen in women with POP [5153].…”
Section: Animal Models Of Popmentioning
confidence: 99%